From Client to Partner: Negotiating the Meaning of Power Asymmetry in Communication Between Worker Parents and Daycare Organizers - Kantun, I Komang; Widiada, I Gede; Sutama, I Wayan (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relations, 2025)
The relationship between the parents of the workers and the daycare manager is frequently characterized as evolving from a client-service provider dynamic to a partnership. This qualitative case study conducted at Koala Daycare in Jimbaran challenges the linear narrative by uncovering the complexity of meaning and power negotiation. Through comprehensive observations and interviews with both parents and managers, analyzed using Giddens' Structuration Theory and the Coordinated Management of Meaning (CMM), this study reveals that power relations are dynamic and subject to continuous negotiation. The findings indicate that communication forms a cyclical process, beginning with the negotiation of written rules, followed by the power struggle among experts during the initiation stage, the selective openness of parents, and the paradox of CCTV technological transparency, which simultaneously fosters trust and serves as a supervisory mechanism. The critical conclusion is that what emerges is not a genuine partnership but rather a "pseudo-partnership"—a fragile social order perpetually maintained through the coordination of meaning in everyday communication, amid the tension between transactional and collaborative logic.